Blackout eaudiobook A novel. - Clayton, Dhonielle (Blackout, 2021)
2022 Audie Award Winner! Six critically acclaimed, bestselling, and award-winning authors bring the glowing warmth and electricity of Black teens in love to this charming, hilarious, and heartwarming novel that shines a bright light through the dark. This full-cast audio edition is performed by Joniece Abbott-Pratt, Dion Graham, Imani Parks, Jordan Cobb, Shayna Small, A.J Beckles, and Audible Hall-of-Famer Bahni Turpin. A summer heatwave blankets New York City in darkness. But as the city is thrown into confusion, a different kind of electricity sparks... A first meeting. Long-time friends. Bitter exes. And maybe the beginning of something new. When the lights go out, people reveal hidden truths. Love blossoms, friendship transforms, and new possibilities take flight. Beloved authors—Dhonielle Clayton, Tiffany D. Jackson, Nic Stone, Angie Thomas, Ashley Woodfolk, and Nicola Yoon—celebrate the beauty of six couples and the unforgettable magic that can be found on a sweltering starry night in the city.